2010
DOI: 10.1177/1046496410373627
|View full text |Cite
|
Sign up to set email alerts
|

Managers’ Trait Emotional Intelligence and Group Outcomes: The Case of Group Job Satisfaction

Abstract: The purpose of this study is to extend the emerging literature on the effects of managers’ emotional skills on group outcomes. Specifically, the authors propose and test a theoretical model that examines impact of managers’ trait emotional intelligence (EI) on group job satisfaction. Data are based on middle managers and their immediate team members from public service organizations. Results, using Bayesian path analysis, indicate that middle managers’ trait EI has a significant indirect effect on group job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
0
22
1
Order By: Relevance
“…Furthermore, the same analysis revealed that the emotionally intelligent management “triggers» proactivity [ 20 ], the team empowerment [ 20 , 23 ], patient satisfaction of care provided [ 16 ], wellbeing at work [ 21 ] and contributes decisively to pay extra effort on the part of subordinates, efficiency and job satisfaction [ 17 , 18 ]. Developed emotional skills of leaders and followers, are instrumental in achieving a healthy work environment, not only in the healthcare field but also in ministries, public services, security bodies, private companies, industries, schools, reinforce organizational commitment [ 36 - 39 ], job satisfaction [ 36 - 38 , 40 , 41 ] and wellbeing in the workplace [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the same analysis revealed that the emotionally intelligent management “triggers» proactivity [ 20 ], the team empowerment [ 20 , 23 ], patient satisfaction of care provided [ 16 ], wellbeing at work [ 21 ] and contributes decisively to pay extra effort on the part of subordinates, efficiency and job satisfaction [ 17 , 18 ]. Developed emotional skills of leaders and followers, are instrumental in achieving a healthy work environment, not only in the healthcare field but also in ministries, public services, security bodies, private companies, industries, schools, reinforce organizational commitment [ 36 - 39 ], job satisfaction [ 36 - 38 , 40 , 41 ] and wellbeing in the workplace [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study paid close attention to trait EI assessed via a self-report questionnaire. A substantial body of research has demonstrated that trait EI is essential and important for job-related well being (Zampetakis and Moustakis, 2010;Fu, 2014;Schutte and Loi, 2014;Petrides et al, 2016;Clarke and Mahadi, 2017;Sun et al, 2017). Moreover, a meta-analysis study revealed that EI was positively correlated with job satisfaction (Miao et al, 2016(Miao et al, , 2017.…”
Section: Trait Emotional Intelligence and Job Satisfactionmentioning
confidence: 99%
“…Conversely, more autonomous teams may have fewer opportunities for the leader to display emotions, which can result in lower follower-trust relationships ( Tee, 2015 ) and lower levels of leader-induced emotional contagion. An example of this appraisal is seen in the study by Zampetakis and Moustakis (2011) , where researchers observed that a group’s evaluative judgment of their leader’s emotional intelligence mediated the relationship between the leader’s actual emotional intelligence and the group’s job satisfaction measures.…”
Section: Level 4 (Groups and Teams): The Locus Of Emotional Contagionmentioning
confidence: 99%